2016
DOI: 10.21037/jtd.2016.04.59
|View full text |Cite
|
Sign up to set email alerts
|

Nm23-H1 was involved in regulation of KAI1 expression in high-metastatic lung cancer cells L9981

Abstract: Background:The tetraspanin KAI1/CD82 was identified as a tumor metastasis suppressor that downregulated in malignant progression of lung cancer. However, the underlying mechanism of anti-metastasis role of KAI1 in lung cancer is hardly known. In this paper, we sought to study the function and regulatory mechanism of KAI1 in high metastasis lung cancer cell line.Methods: KAI1 expression was detected in high/low metastatic large lung cancer cell line L9981/NL9980 by quantitative real-time polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…70 Further, KAI-1 expression was regulated through Nm23-H1 through modulation of KAI-1 promoter activity in L9981 lung cancer cells. 71 Another study showed that c-Myc can upregulate the expression of Nm23-H1. 72 Furthermore, the oncoprotein ErbB2 expression was shown to be regulated by Nm23-H1, which affects the cell proliferative activity of ErbB2.…”
Section: Transcription Regulation Of Cellular Targets By Nm23 H1mentioning
confidence: 99%
“…70 Further, KAI-1 expression was regulated through Nm23-H1 through modulation of KAI-1 promoter activity in L9981 lung cancer cells. 71 Another study showed that c-Myc can upregulate the expression of Nm23-H1. 72 Furthermore, the oncoprotein ErbB2 expression was shown to be regulated by Nm23-H1, which affects the cell proliferative activity of ErbB2.…”
Section: Transcription Regulation Of Cellular Targets By Nm23 H1mentioning
confidence: 99%
“…The gene encoding NM23-H1 is a suppressor of tumor metastasis; research has revealed that it may reduce MMP-2 and -9 expression in various types of cancer cells (18)(19)(20)(21)35,42,43). Boissan et al (19) previously reported that NM23-H1 silencing promotesthe extracellular matrix invasion of HepG2 cells by up regulating numerous MMPs, including MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…When transfected with NM23 genes, a variety of tumor cell types were reported to exhibit the inhibition of metastatic properties, including migration, invasion, and colonization (14)(15)(16)(17)(18). The NM23-H1 (NME1) gene was reported to be the one closely associated with the metastasis of cancer cells, including breast, lung and liver cancer (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of nm23 in human cancer is currently unconfirmed (22,(28)(29)(30)(31), and certain reports have indicated there is a link between high expression of the nm-23 gene and its protein product with low metastatic potential of cancer (28). Nm-23 is known to be associated with early onset of familial breast and ovarian cancer (28).…”
Section: Discussionmentioning
confidence: 99%